A highly conserved cryptic epitope in the receptor binding domains of SARS-CoV-2 and SARS-CoV - Yuan, Meng; Wu, Nicholas C.; Zhu, Xueyong; Lee, Chang-Chun D.; So, Ray T. Y.; Lv, Huibin; Mok, Chris K. P.; Wilson, Ian A. (Science (American Association for the Advancement of Science), 2020)
The surface of severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2) is decorated with trimeric spikes that bind to host cell receptors. These spikes also elicit an antibody response, so understanding antibody recognition may aid in vaccine design. Yuan et al. determined the structure of CR3022, a neutralizing antibody obtained from a convalescent SARS-CoV–infected patient, in complex with the receptor-binding domain of the SARS-CoV-2 spike. The antibody binds to an epitope conserved between SARS-CoV-2 and SARS-CoV that is distinct from the receptor-binding site. CR3022 likely binds more tightly to SARS-CoV because its epitope contains a glycan not present in SARS-CoV-2. Structural modeling showed that the epitope is only revealed when at least two of the three spike proteins are in a conformation competent to bind the receptor. Science , this issue p. 630 Structural studies show that a SARS antibody binds a conserved epitope on the viral spike distinct from the receptor-binding site. The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2) has now become a pandemic, but there is currently very little understanding of the antigenicity of the virus. We therefore determined the crystal structure of CR3022, a neutralizing antibody previously isolated from a convalescent SARS patient, in complex with the receptor binding domain (RBD) of the SARS-CoV-2 spike (S) protein at 3.1-angstrom resolution. CR3022 targets a highly conserved epitope, distal from the receptor binding site, that enables cross-reactive binding between SARS-CoV-2 and SARS-CoV. Structural modeling further demonstrates that the binding epitope can only be accessed by CR3022 when at least two RBDs on the trimeric S protein are in the “up” conformation and slightly rotated. These results provide molecular insights into antibody recognition of SARS-CoV-2.